(untitled) (World Bulletin of Public Health, 2024)
The study is devoted to the urgent problem of the psychological state, coping behavior and psychological resources of students during distance learning in 2020. The problem of coping behavior has been studied for more than a decade, however, during the COVID-19 pandemic, this problem attracted the special attention of many researchers. Every resident of the country, and even the world, asked himself questions: how to cope with the variety of emotions that arise in new non-standard situations? How should I behave? How to react? What is the optimal behavior in this particular situation? And no one found an unambiguous answer to the questions posed. The situation during the pandemic developed in different ways, which again caused a diverse range of emotions among residents of cities and countries: those who studied and worked during this period, who were ill, and those who were forced to isolate themselves.